Mechanics of materials - Hibbeler, R. C. (Pearson, 2017)
Mechanics of Materials clearly and thoroughly presents the theory and supports the application of essential mechanics of materials principles. The Tenth Edition retains the hallmark features synonymous with the Hibbeler franchise, but has been enhanced with the most current information, a fresh new layout, added problem solving, and increased flexibility in the way topics are covered.